The Effect of Numbers Puzzle Games on the Cognitive Development of Preschool Children Aged 5-6 Years at RA Nurul Hidayah Malang - Bagus Tyas Anggoro; Ikit Netra (Indonesian Health Journal, 2022)
Various factors, including the lack of stimulus from parents, can influence deviations in cognitive development in children. A number puzzle game is one of several stimuli in improving children’s cognitive development. This study aims to determine the effect of a number puzzle game on the cognitive development of preschool children aged 5-6 years. The type of research used in this study is a pre-experimental design with one group pre-test and post-test designs. The research instrument used was a checklist for assessing the cognitive abilities of children aged 5-6 years. The sampling technique used in this study is the total sampling technique of 22 children. The data analysis technique used the Wilcoxon signed rank test using the SPSS application. The results showed an effect of number puzzle games on the cognitive development of preschool children aged 5-6 years at RA Nurul Hidayah Pemalang (p-value 0.000, p-value <0.05). Based on the results of the study, it can be concluded, namely: 1.) Age and gender characteristics obtained the results of most respondents aged six years as many as 12 children (54.5%), with the majority being male as many as 12 children (54.5%). 2.) Children’s cognitive development before puzzle game therapy was carried out, the results were that almost most children were in the undeveloped category